A Conflicted Nation. Storia dell'Italia nella Guerra Fredda (1943–1978). Issue 3 (27th May 2018) - Gilbert, Mark
Abstract: This roundtable assesses the arguments and importance of Guido Formigoni's book  Storia dell'Italia nella Guerra Fredda (1943 – 19 78) . This book is essentially composed of seven 70–80-page broadly chronological chapters, each of which might almost be expanded into a short book in its own right. The chapters perform the difficult feat of shifting constantly between the foreign policy of the Italian state (which was so often driven by domestic political considerations) and the political consequences of international events on the debates (or polemics) taking place in the Italian polity. There can be few works of international history in which the linkage between the domestic and foreign policy 'levels' is so clearly demonstrated. Indeed, one of the key objectives of the book plainly is to show that although there may be countries where foreign policy is carried on with blithe indifference to domestic politics, Italy is certainly not one of them, or was not during the Cold War years. Mark Gilbert introduces the book on which Federico Romero, Maud Bracke and Michele Marchi engage in a detailed commentary, to which the author replies.